Accounting, Economics, and Law: A Convivium (De Gruyter, 2011)
The Journal of Accounting, Economics, and Law: A Convivium (AEL) aims to encourage a comprehensive understanding of the relationship between individuals, organizations, and institutions in economy and society. Among other matters, attention will be paid to financial, economic, and legal methods and languages that have an important albeit neglected role in this relationship.